HUBUNGAN SUHU RUANG DENGAN KEJADIAN PENYAKIT DEMAM BERDARAH DIKELURAHAN PONTAP KECAMATAN WARA TIMUR, PALOPO - Sarfa Hafid; Musdalifah Syamsul (UNM Environmental Journals, 2021)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the Dengue virus through mosquito vectors which is still a public health problem in Indonesia. Climatic factors such as temperature and humidity have an important role in the breeding process of the mosquito vector that spreads DHF. When changes in temperature and humidity occur, it can affect vector density and the potential for disease transmission where Ae. aegypti mosquitoes require a good environment to breed. The BMKG states that extreme climate change risks an increase in DHF cases. The aim of this study was to analyze the relationship between temperature and DHF cases in Bahontula Village, Petasia District, North Morowali Regency. This type of research is analytic using a case control research design. The research sample was 112 respondents, taken randomly using simple random sampling. How to collect data with questionnaires and observations. The statistical test used is the α test. The results showed that there was a relationship between temperature and DHF cases (p=0.019); (OR = 0.319). The conclusion of this study is that the temperature factor is related to DHF cases. For the Bahontula subdistrict, it is necessary to increase awareness of residents and the need for cooperation with the BMKG to provide information related to changes in temperature. When mosquitoes are at a good temperature for breeding, people must keep the environment clean, such as doing 3MPlus.